Close Binaries with delta Scuti components: New discoveries, analysis techniques and recent results - Liakos, A.; Niarchos, P.; Gazeas, K. (10th Hellenic Astronomical Conference, 2012)
The results from a four-year systematic observational sky survey of eclipsing binaries, candidates for containing a delta Scuti component, are presented. More than a hundred systems were tested for a possible oscillating behavior, 17 out of which were found to show evidence of pulsating component and 8 more being ambiguous cases for further research. Data analysis and modelling methods are described step-by-step, and as an example the case of BO Her is presented in detail. Using the observational results of all known close binaries with a delta Scuti component collected from the literature and our own study, a total of 73 such systems is gathered. Correlations among their physical parameters (e.g. pulsation and orbital periods, evolutionary status) are also derived, extending significantly our knowledge of these systems.